Nurses' performance in the care of the prevention and treatment of pressure injuries (Research, Society and Development, 2020)
Objective: to know the role of nurses in the prevention and treatment of pressure injuries in the hospital environment. Methodology: a qualitative study of the descriptive and exploratory type. Twelve nurses from a hospital in the interior of Rio Grande do Sul participated in the study. Data collection took place in September 2018, through the semi-structured interview, with the data analyzed by Thematic Content Analysis. Results: there is evidence of the use of care strategies with a focus on prevention: skin assessment, measures to reduce pressure on bone prominences and hygienic care. Regarding the treatment, the following stand out: use of specific coverings according to the characteristics of the lesion, hydration and nutritional support, combined with pressing education meetings. Conclusion: the role of nurses in caring for patients with injuries is based on prevention and treatment, using innovative care technologies, providing safe care, reducing hospital stay and enabling an improvement in the patient's quality of life and health.